International development illusions and realities - Black, Maggie (Ottawa Between the Lines, 2015)
Development is often misunderstood and can embrace everything from large infrastructure projects to small-scale environmental initiatives. The idea can often mask confusion, contradiction, deceit and corruption. This book is essential reading for anyone wanting to know what development actually is. It covers all the key themes and critically suggests ways to bring the poor and marginalised into the process.
Includes index.
Keywords: Economic assistance--Developing countries